A governança educativa local: a alfabetização pelas direções provinciais em Angola - Mendes, Carolina (2015)
The considerations presented in this research emerged from a larger research project, still in development, on new cooperation agents and their action in the area of education. It’s a work that aims to understand flows of cooperation practices for development, rarely accounted for by international cooperation institutions. Based on the implementation of the Program for Literacy and School Acceleration (SAAP) in Angola, the investigation focuses on government (or not) social partnerships in the context of literacy and in understanding if they are to be a development catalyst from the point of view of the agents involved using the analysis of the work of three types of institutions, such as: private, religious and NGOs. This communication feeds on the base idea that to do is to think, as mentioned by Richard Sennett, and that the subjects can become competent interpreters of experience. This time we present an analysis of the education policies in adult education in Angola, referenced on not only the concept of Sennett’s Dialogic Cooperation (2012) as well as on Kissler & Heidemann’s concept of Governance (2006). It is this theoretical double, we observe and analyze some of the data collected in Angola during the month of March (2015) on a field visit to Zaire, Malange, Kwanza South and Benguela. Framed in a qualitative methodology and through a content analysis of three semi-structured interviews to three provincial coordinators of the SAAP, we are presented evidences on several dimensions, in particular as regards the establishment of partnerships, their formalization, the implementation of the SAAP, the people who attend it, their monitoring, the challenges and innovations that emerge.